Peran Kontrol Diri dalam Dinamika Perilaku Bullying di Lingkungan Sekolah - Moch Syahirul Alam Bagasul Ulum; IGAA Noviekayati; Amherstia Pasca Rina (JIWA: Jurnal Psikologi Indonesia, 2026)
Bullying behavior is one of the problems that is often found in the world of education. In the data from the Indonesian Child Protection Commission (KPAI) in the period 2020-2023 there were 1,916 reports related to bullying cases in the field of education and continued to increase. Based on previous research, there are internal and external factors of bullying behavior. One of them is self-control. This study examines the relationship between self-control and bullying behavior in schools. The study population included 122 students in one of the junior high schools in Sidoarjo. The sampling technique used accidental sampling. This study uses the product moment approach method which shows that there is a significant negative relationship between self-control and bullying behavior (rxy = 0.495, p < 0.001) which means that if the level of self-control is high, the level of bullying behavior is low and vice versa. This finding underlines the importance of self-control in reducing bullying behavior and highlights the need for various aspects of both the school, environment, and parents in improving self-control in children or students. Keywords: Self-control, Bullying Behavior, Students, Junior High School Perilaku bullyiing merupakan salah satu permasalahan yang sering ditemui pada dunia pendidikan. Pada data Komisi Perlindungan Anak Indonesia (KPAI) dalam kurun waktu 2020-2023 terdapat 1.916 laporan terkait kasus bullying di bidang Pendidikan dan terus meningkat. Berdasarkan penelitian sebelumnya, terdapat faktor internal dan eksternal dari perilaku bullying. Salah satunya adalah kontrol diri. Penelitian ini meneliti hubungan antara kontrol diri dengan perilaku bullying di sekolah. Populasi penelitian mencakup 122 Siswa di salah satu SMP di Sidoarjo. Teknik pengambilan sampel menggunakan accidental sampling. Penelitian ini menggunakan metode pendekatan product moment yang menunjukkan bahwa terdapat hubungan negatif signifikan antara kontrol diri dengan perilaku bullying (rxy=-0,495, p < 0,001) yang artinya jika tingkat kontrol diri tinggi, maka tingkat perilaku bullying rendah dan begitupun sebaliknya. Temuan ini menggarisbawahi pentingnya kontrol diri dalam mengurangi perilaku bullying dan menyoroti perlunya berbagai macam aspek baik pihak sekolah, lingkungan, maupun orangtua dalam meningkatkan kontrol diri pada anak atau siswa. Kata kunci: Kontrol diri; Perilaku Bullying; Siswa; SMP